Comparison of symptoms of depression, anxiety, and stress in postpartum women with and without pain: a network analysis - Yanchi Wang; Kai Mao; Jianhua Deng; Jian Gu (BMC Pregnancy and Childbirth)
Abstract Background Postpartum pain may worsen new mothers’ psychological distress but is understudied. This study used network analysis to compare depression, anxiety, and stress symptom networks in postpartum women with and without pain. Methods A total of 1153 postpartum women were grouped according to pain status: the no-pain group (n = 594) and the pain group (n = 559). Depression assessed using the Edinburgh Postnatal Depression Scale (EPDS), anxiety via the DASS-21 anxiety subscale, and stress through the Maternal Postpartum Stress Scale (MPSS). Network analysis was employed to estimate and compare the symptom networks between the two groups, identifying central symptoms connecting different symptom clusters, and network comparison tests were conducted to assess differences in global and local network structures. Results In the no-pain group, the most central symptoms were E8 (“I have felt sad and miserable”), M19 (“Lack of time for myself”), and M15 (“Insufficient enjoyment in sexual intercourse”). In the pain group, the top central symptoms were E5 (“I have felt scared or panicky for no very good reason”), M15, and E8. Network comparison tests indicated no significant differences in global structure (M = 0.132, P = 0.908) or overall connectivity strength (S = 0.262, P = 0.374). In the non-pain group, the item with the highest predictability is D5 (“I felt I was close to panic”), while in the pain group, it is E4 (“I have been anxious or worried for no good reason”). Conclusions Postpartum pain modulates symptom networks, especially in body image and time management. Tailored interventions for pain - related distress are needed, and targeting central symptoms can improve maternal mental health.